PENDIDIKAN NILAI-NILAI MORAL PESERTA DIDIK MELALUI EKSTRAKURIKULER PRAMUKA KELAS IV DI UPT SD NEGERI 112 GRESIK - nurul komariyah; Nataria Wahyuning Subayani (JUSEDA, 2022)
Character education is education that instills and develops character in students, applies and practices it in life both in the school, family and community environment. This character building is done through scout extracurricular activities. The purpose of this study was to determine the moral character and behavior of students through scout extracurricular activities in class IV UPT SD Negeri 112 Gresik, with a total of 10 students, namely five boys and five girls. This type of research is a qualitative descriptive research. data collection methods by observation, interviews and questionnaires. The results of this research indicate that character education carried out through scout extracurricular activities is expected to be able to create moral character that includes religious values, honesty, discipline, independence, responsibility, and social care. With the education of moral values of students through scout extracurriculars, it is hoped that students will be able to understand scouting values, for example, help, independence, discipline, and responsibility and can make them better individuals and can be applied in everyday life.